The Impact Of Work Ethic, Work Culture, And Motivation On Performance Through Performance Allowance At The Center For Social Welfare Education And Training, Yogyakarta - Enri Pamawan; Kusuma Chandra Kirana; Didik Subiyanto (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The Yogyakarta Social Welfare Education and Training Center is currently facing challenges in optimizing employee performance due to the Covid-19 pandemic. To answer these problems, researchers conducted a study to analyze the impact of work ethic, work culture, and motivation on employee performance allowance at the center. Data collection was conducted using a questionnaire, and two test tools, namely validity test and reliability test, were used to ensure the accuracy and reliability of the questionnaire. The analysis used indicator tests, hypothesis testing, and Patial Least Square (PLS). The hypotheses proposed and tested include the positive influence of work ethic, work culture, and motivation on employee performance benefits and employee performance itself. The study concluded that there is a positive relationship between these variables and employee performance, indicating that improving work ethic, work culture, and motivation can result in better performance and better performance allowance for employees at the center.